The influence of microbial isoflavonoid specific metabolites on platelets and transition metals iron and copper - Migkos, Thomas; Applová, Lenka; Horký, Pavel; Tvrdý, Václav; Karlíčková, Jana; Macáková, Kateřina; Hrubša, Marcel; Catapano, Maria Carmen; Tomanek, Magdalena; Pour, Milan; Mladěnka, Přemysl (Phytomedicine, 2019)
BACKGROUND: Isoflavonoids seem to possess positive cardiovascular and other beneficial effects in humans. HYPOTHESIS: Their low bioavailability, however, indicates that small isoflavonoid metabolites formed by human microflora can significantly contribute to these activities. STUDY DESIGN: Testing antiplatelet activity ex vivo in human blood and interaction with transition metals in vitro. METHODS: The effect on platelet aggregation induced by different triggers (arachidonic acid, collagen, ADP, TRAP-6), and interactions with transition metals (iron and copper chelation/reduction) were evaluated against four isoflavonoid-specific metabolites: S-equol; O-desmethylangolensin; 2-(4-hydroxyphenyl) propionic acid (HPPA); and 4-ethylphenol. RESULTS: S-equol, 4-ethylphenol and O-desmethylangolensin blocked platelet aggregation induced by arachidonic acid and collagen. S-equol even matched the potency of acetylsalicylic acid in the case of collagen, which is the most physiological inducer of aggregation. Moreover, their effects in general seemed to be biologically relevant and attainable at achievable plasma concentrations, with the exception of HPPA which was ineffective. While only O-desmethylangolensin mildly chelated iron and copper, all four compounds markedly reduced cupric ions. Their direct free radical scavenging effects seem to have little clinical relevance. CONCLUSION: This study has shown that S-equol, O-desmethylangolensin and 4-ethylphenol, arising from isoflavonoid intake, can have biologically relevant effects on platelet aggregation.
Keywords: equol; železo; Biological Availability; Aspirin; Platelet Aggregation; fenoly; trombocyty; Phenols; biologická dostupnost; lidé; Isoflavones; měď; agregace trombocytů; Blood Platelets; Copper; Male; Iron; isoflavony; mužské pohlaví; Equol; Humans